Job Market and Reforms of Labor Legislation in Spain - Cruz Villalón, Jesús (2016)
The present article talks about the next relevant issues. In the first part of the article it refers to the impact the crisis economic had in Spain’s job market. In the second part it refers to a versus between structural and conjectural reforms. The third section sets out the issue concerning the pressures that cause wage devaluation. In the fourth section, the new rules of external flexibility are analyzed. Then, the sixth section examine the rules concerning internal flexibility. And finally, the seventh section discusses the absence of social dialogue and the new European governance.